2020
DOI: 10.1155/2020/7605160
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Protects N2a Cells against Aβ Toxicity In Vitro

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disease. Aβ plays an important role in the pathogenesis of AD. Sodium butyrate (NaB) is a short-chain fatty acid salt that exerts neuroprotective effects such as anti-inflammatory, antioxidant, antiapoptotic, and cognitive improvement in central nervous system diseases. The aim of this study is to research the protective effects of NaB on neurons against Aβ toxicity and to uncover the underlying mechanisms. The results showed that 2 mM NaB had a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Butyrate can also interfere with Aβ1-40 oligomerization and exert multiple effects against neuropsychiatric disorders as an inhibitor of HDAC, which can improve cognitive memory performance in a 5 × FAD mouse at an early disease stage (Griseri et al, 2003;Ho et al, 2018;Fernando et al, 2020). Sun et al (2020b) found that butyrate protects N2a cells from Aβ-induced cell damage by activating GPR109A in vitro. Our previous studies also demonstrated that butyrate could exert neuroprotective effects on depression, PD, AD and traumatic brain injury in model mice (Liu et al, 2015;Sun et al, 2015Sun et al, , 2016aSun et al, ,b, 2020aLi et al, 2016).…”
Section: Metabolic Dysfunctionsmentioning
confidence: 97%
“…Butyrate can also interfere with Aβ1-40 oligomerization and exert multiple effects against neuropsychiatric disorders as an inhibitor of HDAC, which can improve cognitive memory performance in a 5 × FAD mouse at an early disease stage (Griseri et al, 2003;Ho et al, 2018;Fernando et al, 2020). Sun et al (2020b) found that butyrate protects N2a cells from Aβ-induced cell damage by activating GPR109A in vitro. Our previous studies also demonstrated that butyrate could exert neuroprotective effects on depression, PD, AD and traumatic brain injury in model mice (Liu et al, 2015;Sun et al, 2015Sun et al, , 2016aSun et al, ,b, 2020aLi et al, 2016).…”
Section: Metabolic Dysfunctionsmentioning
confidence: 97%
“…The SCFAs propionic acid, butyric acid, and valeric acid were observed to inhibit the aggregation of both monomer Aβ 1-40 and Aβ 1-42 into Aβ oligomers and Aβ fibrils [ 130 ]. Moreover, sodium butyrate was shown to promote mitochondrial function and cell proliferation, which ameliorates Aβ-induced N2a cell damage [ 131 ]. In addition, sodium propionate showed a protective effect against Aβ-induced neurotoxicity by inhibiting the production of inducible nitric oxide synthase and cyclooxygenase-2 (COX-2) [ 132 ].…”
Section: Scfas and Admentioning
confidence: 99%
“…In addition, sodium propionate showed a protective effect against Aβ-induced neurotoxicity by inhibiting the production of inducible nitric oxide synthase and cyclooxygenase-2 (COX-2) [ 132 ]. In amyloidogenic APP processing, sodium butyrate can decrease the expression of APP and increase NEP expression levels [ 131 ]. However, sodium butyrate has also been shown to enhance neuronal apoptosis induced by the APP C-terminal fragment (C31, AICD, and C99) by lowering histone deacetylation to regulate gene transcription [ 133 ].…”
Section: Scfas and Admentioning
confidence: 99%
“…Although the mechanisms by which the gut microbiota contributes to brain health remain largely unknown, emerging data show that microbial metabolites are a possible link (Vogt et al, 2018 ; Fujii et al, 2019 ; Konjevod et al, 2020 ; Zhuang et al, 2021 ; Doifode et al, 2021 ). For example, short chain fatty acids (SCFAs, such as acetate, propionate, and butyrate) are the major beneficial metabolites produced by healthy microbiota; they exhibit beneficial effects on the brain, including a reduction in AD pathology, in several animal models (Mishra et al, 2020 ; Sun et al, 2020 ; Wenzel et al, 2020 ). Indeed, the abundance of SCFAs is often reduced in the gut of patients with AD and MCI, while healthy dietary habits, like a ketogenic diet, increase their production (Nagpal et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%